High strength and high ductility copper obtained by topologically controlled planar heterogeneous structures. (November 2016) - Liu, Xiaowei; Wu, Kai; Wu, Ge; Gao, Yuan; Zhu, Linli; Lu, Yang; Lu, Jian
Abstract: By using topologically controlled surface mechanical attrition treatment (SMAT), we processed annealed copper (Cu) and obtained an improved strength without sacrifice of ductility. The partially SMAT process demonstrated its ability to introduce a planar heterogeneous structure in the Cu, while the hardness measurements and microstructure characterization showed that the "hard phase" SMATed areas were embedded in the "soft matrix" of coarse grained Cu, forming a unique bimodal structure combined with both coarse grains and nano-twinning grains, contributing to the overall strengthening. Finite element simulation and theoretical modeling were performed to explain the underlying mechanism for the material property enhancement. Graphical abstract: